An eight-year-old girl with autoimmune polyglandular syndrome type3A that developed during the course of primary Epstein–Barr virus (EBV) infection: clinical implication of EBV in autoimmune thyroid disease - Shizuka Kirino; Hisae Nakatani; Aoi Honma; Asami Shinbo; Keiko Onda; Mari Okada; Masako Imai; Natsuko Suzuki; Akihiro Oshiba; Masayuki Nagasawa (Immunological Medicine, 2020)
An eight-year-old girl was admitted for prolonged fever and general fatigue. Bilateral reddened and swollen tonsils covered with white fur and increased numbers of atypical lymphocytes in blood led to a diagnosis of infectious mononucleosis (IM) due to primary Epstein–Barr virus (EBV) infection, which was confirmed by a positive anti-EBV viral capsid antigen IgM antibody reaction. She had a swollen thyroid gland and glycosuria at admission, which persisted after IM resolved. Undetectable thyroid-stimulating hormone (TSH), increased thyroid hormone and elevated HbA1c levels led to a diagnosis of autoimmune polyglandular syndrome type3A, based on the presence of antibodies for TSH receptor and glutamic acid decarboxylase. The clinical significance of EBV infection in the development of autoimmune endocrine disorders has been discussed.